Improving Carotenoid Extraction from Tomato Waste by Pulsed Electric Fields - Luengo, Elisa; Álvarez, Ignacio; Raso, Javier (Frontiers in Nutrition, 2014)
In this investigation, the influence of the application of Pulsed Electric Fields (PEF) of different intensities (3-7 kV/cm and 0-300 μs) on the carotenoid extraction from tomato peel and pulp in a mixture of hexane:acetone:ethanol was studied with the aim of increasing extraction yield or reducing the percentage of the less green solvents in the extraction medium. According to the cellular disintegration index, the optimum treatment time for the permeabilization of tomato peel and pulp at different electric field strengths was 90 µs. The PEF permeabilization of tomato pulp did not significantly increase the carotenoid extraction. However, a PEF-treatment at 5 kV/cm improved the carotenoid extraction from tomato peel by 39 % as compared with the control in a mixture of hexane:ethanol:acetone (50:25:25). Further increments of electric field from 5 to 7 kV/cm did not increase significantly the extraction of carotenoids. . The presence of acetone in the solvent mixture did not positively affect the carotenoid extraction when the tomato peels were PEF-treated. Response surface methodology was used to determine the potential of PEF for reducing the percentage of hexane in a hexane:ethanol mixture. The application of a PEF-treatment allowed reducing the hexane percentage from 45 to 30 % without affecting the carotenoid extraction yield. The antioxidant capacity of the extracts obtained from tomato peel was correlated with the carotenoid concentration and it was not affected by the PEF-treatment.